2012
DOI: 10.1016/j.jneumeth.2012.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MRI of Gd-albumin delivery to the rat hippocampus in vivo by convection-enhanced delivery

Abstract: Convection enhanced delivery (CED) shows promise in treating neurological diseases due to its ability to circumvent the blood-brain barrier (BBB) and deliver therapeutics directly to the parenchyma of the central nervous system (CNS). Such a drug delivery method may be useful in treating CNS disorders involving the hippocampus such temporal lobe epilepsy and gliomas; however, the influence of anatomical structures on infusate distribution is not fully understood. As a surrogate for therapeutic agents, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…It is expected that this percentage would increase with increasing infusion volume. These CED diversion effects are consistent with our previous CED tracer studies [16,17,32] where hyperintense regions were observed within and surrounding the hippocampal fissure in MR imaging, and high concentration of dye at the fissure surface was also shown in histological images. Also, the final CED distribution volume ratios decreased 16.5% in the dorsal hippocampus and 13.2% in the ventral hippocampus when fissures were accounted for in the model.…”
Section: Ced Model Predictionssupporting
confidence: 91%
See 4 more Smart Citations
“…It is expected that this percentage would increase with increasing infusion volume. These CED diversion effects are consistent with our previous CED tracer studies [16,17,32] where hyperintense regions were observed within and surrounding the hippocampal fissure in MR imaging, and high concentration of dye at the fissure surface was also shown in histological images. Also, the final CED distribution volume ratios decreased 16.5% in the dorsal hippocampus and 13.2% in the ventral hippocampus when fissures were accounted for in the model.…”
Section: Ced Model Predictionssupporting
confidence: 91%
“…In previous MR studies, our group has experimentally measured CED into dorsal and ventral rat hippocampi [17,22,32]. Quantification of in vivo concentration patterns during CED was achieved through dynamic contrast enhanced MRI (DCE-MRI) by using measured relaxivities [17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations